(untitled) (ART AND CULTURE BULLETIN, 2025)
The article analyzes the development of cinematographic styles in Uzbek feature films through the example of the subjective camera. I. Lutfullayevʼs visual styles are examined from an art studies perspective, exploring their dramaturgical function, expressive potential, and system of visual imagery.